As bad as they say? : three decades of teaching in the Bronx - Mayer, Janet Grossbach (Book collections on Project MUSE., 2011)
"Rundown, vermin-infested buildings; rigid, slow-to-react bureaucratic systems; children from broken homes and declining communities. How can a teacher succeed? How does a student not only survive but also come to thrive? It can happen, and this book tells the heroic stories of the author's students during her 33-year tenure as a Bronx high school teacher. In 1995, her students began a pen-pal exchange with South African teenagers who, under apartheid, had been denied an education. Almost uniformly, the South Africans asked, "Is the Bronx as bad as they say?" This dedicated teacher promised those students and all future ones that she would write a book to help change the stereotypical image of Bronx students and show that, in spite of overwhelming obstacles, they are outstanding young people, capable of the highest achievements. She walks the reader through the decrepit school building, describing the deplorable physical conditions that students and faculty navigate daily. Then, in eight chapters eight amazing young people are introduced, a small sample of the more than 14,000 students the writer has felt honored to teach. She describes her own Bronx roots and the powerful influences that made her such a determined teacher. Finally, the veteran teacher sounds the alarm to stop the corruption and degradation of public education in the guise of what are euphemistically labeled reforms. She also expresses optimism that public education and our democracy can still be saved, urgently calling on all to become involved and help save our schools."--Publisher's abstract.